Regulacje prawne dotyczące hidżabu we współczesnym Iranie - Kuriata, Agnieszka (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Iran is the only country in the world where the obligation to wear hijab results from the Criminal Code and includes all women, including non-Muslims. The author analyzes article 638 of the Criminal Code, its modifications over the last years, and its observance in modern Iran
Keywords: hijab; manteau; chador; roosari; mangae; Iran; article 638 of Iranian Penal Code; Basij; Islam